Doppler effect and one-way speed of light - Čojanović, Miloš (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The Doppler effect is one of the most important and most elementary phenomenon in nature. If we accept that fact, then there is no need to use any other theories to understand its essence. There is only one Doppler effect, regardless of whether the signal between the sender and the receiver travels directly or through a medium. Therefore, there is only one formula that is valid in all cases. The goal of this paper is to determine that formula. Using the obtained results, we will show that the one-way speed of light can be measured by physical experiment.